ANALISA KEGAGALAN LIGHTNING ARRESTER PADA PENYULANG SULAHAN BANGLI - Yodha Bhaskara, I Kadek Agus; Dyana Arjana, I Gede; Suartika, I Made (Jurnal SPEKTRUM; Vol 6 No 3 (2019): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2019.v06.i03.p13, 2019)
In the process of electrical power distribution, various types of interference can occur so that a protection system is needed to maintain the continuity and stability of electrical power distribution. Arrester is one of the main protection systems used to protect electrical equipment against overvoltages caused by lightning strikes. Penyulang Sulahan is a 20kV medium voltage distribution system that gets power supplies from Gianyar Substation 1/60 MVA and is located on a plateau that is prone to natural phenomena such as lightning. During 2016 there were three times the failure of conventional arresters. Based on these data, it is necessary to analyze the failure of arresters at Penyulang Sulahan so that the continuity of electricity can be better. The method used in this study is to collect data in the form of single line diagrams, disturbance data, and large grounding resistance on Sulahan Feeders. Next, compare Metal Oxide Arrester with Multi Chamber Arrester. The results obtained were grounding in the Feeder over 5 ohms which caused conventional arrester to not work properly. Multi Chamber Arrester is an arrester that has no effect on the value of grounding resistance. After installing the Multi Chamber Arrester, failure of arresters has decreased to one failure during 2017